Penerapan Good Corporate Governance Berbasis Nilai Budaya Siri’na Pacce sebagai Solusi Penguatan Tata Kelola Perusahaan - Hirman, Akhmad Akram; Putri, Diana; Hamidah, - (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2024)
Abstract: Implementation of Good Corporate Governance Based on Siri'na Pacce Cultural Values as a Solution for Strengthening Corporate Governance.Objective: This research aims to analyze the implementation of Good Corporate Governance Principle based on Siri’na Pacce values.Method: Case study field research was employed with employees as informants.Results: The implementation of GCG in the company by applying cultural practices of Siri’na Pacce is in accordance with applicable regulations. Novelty: The practice of GCG in the company from a cultural perspective, especially the Siri’na Pacce culture which forms the company’s culture.Contribution: This article provides alternative solution for companies in terms of GCG implementation from the perspective of Siri’na Pacce so that the company can grow rapidly by employing local wisdom. Penerapan Good Corporate Governance Berbasis Nilai Budaya Siri’na Pacce sebagai Solusi Penguatan Tata Kelola PerusahaanTujuan: Penelitian ini bertujuan mengkaji implementasi prinsip GCG berbasis Siri’na Pacce.Metode: Penelitian ini menggunakan studi kasus dengan para karyawan sebagai informan.Hasil: Implementasi prinsip GCG di perusahaan tersebut dengan mempertimbangkan praktik budaya Siri’na Pacce sesuai dengan peraturan yang berlaku. Kebaruan: Praktik GCG pada perusahaan dari perspektif budaya Siri’na Pacce yang membentuk budaya perusahaan.Kontribusi: Artikel ini menjadi solusi bagi perusahaan dalam hal implementasi GCG dari sudut pandang Siri’na Pacce agar perusahaan tersebut dapat berkembang pesat dengan memanfaatkan kearifan lokal.